Exploring the Drivers and Barriers of Entrepreneurship Among Rural Women and Youths - Hamayangwe, Mukwanya Nabusanga; Kumari, Nilanjana (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: Entrepreneurship in rural areas plays a pivotal role in fostering economic growth and addressing socio-economic disparities. This study examines the drivers and barriers to entrepreneurship among women and youth in Chibombo District, Zambia. Methodology/Approach: Employing a mixed-methods approach, the study combines surveys, focus group discussions, and interviews with 169 participants to explore the enabling factors and challenges within the rural entrepreneurial ecosystem. Findings: Key findings reveal that 72% of participants identified economic necessity as a primary driver, 65% acknowledged the role of government support, and 58% cited personal aspirations. Conversely, 78% reported financial constraints, 62% highlighted infrastructural deficits, and 55% noted socio-cultural norms as significant barriers. These findings emphasize the need for tailored policy interventions to empower rural women and youth, enhancing their capacity to contribute to economic development and reducing systemic obstacles. Practical Implications: Recommendations include implementing gender-sensitive training, mentorship programs, and infrastructural improvements to foster an enabling environment for rural entrepreneurship.